Get Brexit done: a comparative analysis of the political discourse during this process - Orrequia Barea, Aroa (2020)
The Brexit process started on 23rd June 2016 when a referendum was held to vote whether the UK was leaving the EU or not. However, it did not become a reality until 31st January 2020, when the UK officially left the EU. Many debates have taken place to reach this agreement between the most influential politicians in the country. The main objective of this paper is to analyse the poli- tical discourse of the two main protagonists of this process: Boris Johnson, the Prime Minis- ter, and Jeremy Corbyn, the leader of the opposition. The analysis is twofold: on the one hand, a linguistic analysis was carried out to compare the word choice of each politician; on the other, Sentiment Analysis techniques were applied to explore the general polarity of the political discourse.